Making the TEN-E regulation compatible with the Green Deal: Eligibility, selection, and cost allocation for PCIs. (September 2021) - Schittekatte, Tim; Pototschnig, Alberto; Meeus, Leonardo; Jamasb, Tooraj; Llorca, Manuel
Abstract: The European Green Deal calls for a revision of the Regulation on guidelines for trans-European energy infrastructure (TEN-E Regulation). The focus of the TEN-E Regulation was on accelerating the development of strategically important projects linking energy networks across the EU, labelled as Projects of Common Interest (PCIs). We provide seven recommendations on how to revise the Regulation to align it with the new full decarbonisation objective. We split the analysis in three parts: the eligibility, selection and cost allocation of PCIs. Regarding eligibility, first, oil networks should be excluded, while the case of gas networks is debatable. Second, power-to-X technologies, electric charging infrastructure and (smart) gas distribution grids could be added to the scope. Regarding selection, first, the Ten-Year Network Development Plan (TYDNP) should be integrated over all energy vectors using an open-source model. Second and third, the scenarios used in the TYNDPs should be subject to the European Commission's approval, while the approval decision for cost-benefit analysis methodologies should be reallocated from the Commission to ACER. Finally, regarding cost allocation, first, cross-border cost allocation decisions should leave all involved jurisdictions with similar benefit-to-cost ratios to increase commitment. Second, affordability should be the only award criterion for European funding. Highlights: The European Green Deal calls for a revision of the TEN-Regulation. Assessment of experiences with the implementation of the TEN-E Regulation. Discussion on how to align the TEN-E Regulation with full decarbonisation. Analysis focussed on eligibility, selection and cost allocation of PCIs. Formulation of seven recommendations.